2022
DOI: 10.26803/ijlter.21.10.7
|View full text |Cite
|
Sign up to set email alerts
|

EFL Pre-service Teachers' Online Reading Strategy Use and their Insight into Teaching Reading

Abstract: The purpose of this study is to investigate the usage of online reading strategies among EFL pre-service teachers in the Education Program and their pedagogical practices in teaching online reading. A total of 107 participants from the English Education program in East Java were involved in this study. A mixed-method design was used as the research approach. For data collection, this present study used the Second Language Online Reading Strategy Inventory (SLORSI) closed-ended questionnaire and semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Research done by Majumdar et al (2021) also found out the description of the students' online reading profiles can be monitored through the use of reading logs integrated with a learning application. Strategies have been used to foster reading motivation, such as inspirational stories, digital reading text, and expository text (Al Sultan, 2023;Laeli et al, 2022;Lestari et al, 2023;Quinonez-Beltran et al, 2023). Encouraging students to nurture their reading logs will make them enjoy reading and develop their capacity for reading.…”
Section: Introductionmentioning
confidence: 99%
“…Research done by Majumdar et al (2021) also found out the description of the students' online reading profiles can be monitored through the use of reading logs integrated with a learning application. Strategies have been used to foster reading motivation, such as inspirational stories, digital reading text, and expository text (Al Sultan, 2023;Laeli et al, 2022;Lestari et al, 2023;Quinonez-Beltran et al, 2023). Encouraging students to nurture their reading logs will make them enjoy reading and develop their capacity for reading.…”
Section: Introductionmentioning
confidence: 99%